Fatores que influenciam o desempenho social corporativo: uma análise multinível com empresas brasileiras e canadenses - Soares, Rômulo Alves (2016)
The study analyzes how organizational features and the institutional environment in which companies operate, may influence their corporate social performance (CSP). Stakeholder Theory says that some business characteristics can be influenced by their groups of interest, and this may affect their willingness to engange in socially responsible practices, reflecting on their CSP. Moreover, these socially responsible practices are also influenced by the institutional environment they operate. According to the business-system approach, there are some key aspects that shape the national business system of a country like corruption, the degree of state interventionism, the degree to which the country adopts a capital market and its educational and job systems. These institutional features end up shaping management practices and hence standardizes the way companies operate, including their decisions about socially responsible practices. In order to evaluate how these financial and institutional characteristics shape CSP, a descriptive and quantitative research was conducted, using secondary data from Brazilian and Canadian companies that ranged from 2007 to 2014. The companies selected were those of utility, oil and gas operations and materials sectors, that were in the Forbes 2000 list in the year 2008. The CSP was calculated using information from sustainability reports published by those companies during the analyzed period. The financial characteristics were taken from annual reports and the institutional aspects were measured by indicators from several international organizations: World Bank, World Economic Forum (WEF), the Heritage Foundation, Transparency Interational and the United Nations Development Programme (UNDP). In order to analyze the data, it was used descriptive statistics, hypothesis testing such as T test and Wilcoxon test, cluster analysis, panel data regression and hierarchical linear regression. The results show that the institutional environment plays a more important role than financial characteristics in determining the CSP. In addition, Brazilian institutional environment allows companies to adopt a more resource oriented strategy than the Canadian environment. The results also show that the Brazilian and Canadian institutional characteristics influence CSP in an opposite way.